El proyecto educativo-ilustrado de Kant - Lafuente, María Isabel (Revista Historia de la Educación Latinoamericana, 2009)
The aim of this text commentary is both to analyze and organize the main pedagogic ideas that constitute Kant`s educational project. The phenomenological method used by him, allows to find out his essential idea and of the human nature, and to examine how the author conceives it as well as to show the educational forms that make possible education in its two components (body and mind), and how they work together to shape the educationally illustrated project of this author. Finally, the article examines the past and current limits and limitations in this project.